2009
DOI: 10.1016/s1880-4276(09)80022-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bepridil on Atrial Electrical Remodeling in Short‐Term Rapid Pacing

Abstract: Introduction: Bepridil is a multi-ion channel blocker similar to amiodarone. Recent clinical studies have indicated that bepridil shows a favorable efficacy for the treatment of atrial fibrillation (AF). The purpose of this study is to evaluate the effectiveness of bepridil for electrical remodeling induced by rapid atrial stimulation particularly in the acute-phase.Methods and Results: We studied 18 pigs subjected to right atrial appendage rapid pacing at 500 beats/min for 3 hours that were randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Previous reports have shown that rapid pacing (acute vs. chronic) cause atrial electrophysiological remodeling in humans (Goette et al, 1996; Daoud et al, 1997; Yue et al, 1999; Hadian et al, 2002), and in different animal models of AF (Yu et al, 1998; Tsuchiya et al, 2009; Laszlo et al, 2011). Our data show that acute or short-term rapid pacing increases vulnerability of HFD-fed guinea pigs to atrial arrhythmogenesis compared to LFD-fed controls.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that rapid pacing (acute vs. chronic) cause atrial electrophysiological remodeling in humans (Goette et al, 1996; Daoud et al, 1997; Yue et al, 1999; Hadian et al, 2002), and in different animal models of AF (Yu et al, 1998; Tsuchiya et al, 2009; Laszlo et al, 2011). Our data show that acute or short-term rapid pacing increases vulnerability of HFD-fed guinea pigs to atrial arrhythmogenesis compared to LFD-fed controls.…”
Section: Discussionmentioning
confidence: 99%